Radicalising Shakespeare: Staging the Sri Lankan Juliet in Julietge Bhumikawa - Warnapala, K. C. P. (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
Through an analysis of the Sri Lankan film, Julietge Bhumikawa (1998) (Illusions of Juliet), I argue that the film radicalizes Shakespeare-inspired film through providing a bold site of enunciation to the character of Juliet. While the Sri Lankan Juliet is cast as mistress, interrogating discourses of purity surrounding not only the original source text—Romeo and Juliet—but the contemporary Sri Lankan society as well, Julietge Bhumikawa reconfigures female gender ideologies by unraveling the nexus between female madness and patriarchal culture.